Efektivitas Teknik Relaksasi Meditasi dalam Mengurangi Tingkat Stres Belajar pada Siswa SMAN 11 Luwu - Nursyamsiah; Imam Pribadi; Ainul Fahmi (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to test the effectiveness of relaxation techniques in reducing learning stress levels in students at SMAN 11 Luwu. Using a quasi-experimental design One-group Pretest-Posttest, the study involved 26 students who showed symptoms of learning stress. Data was collected through observation, interviews and questionnaires Perceived Stress Scale (PSS-10). The intervention was carried out in 8 sessions, incl pretest, 6 treatment sessions, and posttest. The results showed a significant reduction in students' stress levels after the intervention. Before the intervention, 53.8% of students were in the moderate stress category, while after the intervention 88.5% were in the mild stress category and 11.5% reached normal conditions. Analysis Paired Sample T-test showed a significant difference between stress scores before and after intervention (p < 0.05), with an average decrease in score of 12,808 points. These results confirm the effectiveness of relaxation techniques in reducing students' learning stress, providing important reinforcement for the development of stress management programs in educational settings.